Effect of ethephon on hardening of Pachystroma longifolium seedlings - Dranski,João Alexandre Lopes (2013)
Immediately after planting, tree seedlings face adverse environmental and biotic stresses that must be overcome to ensure survival and to yield a desirable growth. Hardening practices in the nursery may help improve seedling stress resistance through reduction of aboveground plant tissues and increased root volume and biomass. We conducted an assay to quantify changes in the morphogenesis following application of ethephon on seedlings of Pachystroma longifolium (Ness) I. M. Johnst.during hardening. The results showed no effect of the ethephon treatments on the number of leaves but a reduction of up to 50% in seedling height increment, and an increase in stem diameter increment of up to 44% with the 600 mg L-1 ethephon treatment, which consequently altered seedling Dickson Quality Index. Our results indicate that ethephon may help to promote desired morphological changes that occur during seedling hardening in nurseries.